Prevalence of limited health literacy and its associated factors in patients with type 2 diabetes mellitus in Perak, Malaysia: a cross-sectional study - Abdullah, Adina (BMJ Open, 2020)
OBJECTIVE: Limited health literacy in patients with type 2 diabetes mellitus (T2DM) led to poorer diabetes knowledge, less medication adherence and increased healthcare cost. The purpose of this paper was to report the prevalence of limited health literacy in patients with T2DM and to identify factors that are associated with it. DESIGN: A cross-sectional study was conducted from January to March 2018; data on patients’ sociodemographic characteristics, diabetes knowledge, perceived social support and health literacy level were collected. Health literacy level was measured using the European Health Literacy Survey Questionnaire (HLS-EU-Q47). SETTING: Patients were recruited from four primary care clinics in Perak, Malaysia. PARTICIPANTS: Adult patients diagnosed with T2DM who attended the study clinics during the study period. PRIMARY OUTCOME VARIABLE: Patients with HLS-EU-Q47 General Index of ≤33 points were classified as having limited health literacy. RESULTS: The prevalence of limited health literacy was 65.3% (n=279). In bivariate analysis, patients’ ethnicity (p=0.04), highest education level (p<0.001), monthly income (p=0.003), having health insurance (p=0.007), English language fluency (p<0.001), Malay language fluency (p=0.021), attending diabetes education sessions (p<0.001), perceived social support (p<0.001) and diabetes knowledge (p=0.019) were factors associated with limited health literacy. In logistic regression, not being fluent in English was associated with limited health literacy (OR=2.36, 95% CI 1.30 to 4.30) whereas having high perceived social support (OR=0.52, 95% CI 0.40 to 0.69) and having attended diabetes education sessions (OR=0.42, 95% CI 0.27 to 0.68) were associated with adequate health literacy. CONCLUSION: The prevalence of limited health literacy is high among patients with T2DM in Perak, Malaysia. Strategies to improve health literacy in these patients must consider the influences of English fluency, attendance at diabetes education sessions and social support, and may need to adopt a universal approach to addressing limited health literacy.